Web Information Systems Engineering - WISE 2005 Workshops WISE 2005 International Workshops, New York, NY, USA, November 20-22, 2005, Proceedings - Guo, Yuanbo; Jun, Woochun; Kaschek, Roland; Krishnaswamy, Shonati; Pan, Zhengxiang; Sheng, Quan Z. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2005)
This book constitutes the joint refereed proceedings of the three workshops held in conjunction with the 6th International Conference on Web Information Systems Engineering, WISE 2005, in New York, NY, USA, in November 2005. A total of 47 papers were submitted to the three workshops, and 28 revised full papers were carefully selected for presentation. The workshop on Web Information Systems Quality (WISQ 2005) - discussing and disseminating research on the quality of WIS and Web services from a holistic point of view - included 7 papers out of 12 submissions. The workshop on Web-based Learning (WBL 2005) accounted for 10 papers from 14 papers submitted - organized in topical sections on tools, models, and innovative applications. The workshop on Scalable Semantic Web Knowledge Base Systems (SSWS 2005) included 11 presentations selected from 21 submissions. Topics addressed are scalable repository and reasoning services, practical Semantic Web applications, query handling and optimization techniques.